On the tunability of quality-factor for optical Tamm plasmon modes. (24th July 2017) - Kumar, Samir; Das, Ritwick
Abstract: We present a comprehensive investigation to ascertain the impact of gold and silver films on modifying the quality-factor (Q-factor) of optical Tamm-plasmon (OTP) resonance in a metal-distributed Bragg reflector (M-DBR) geometry. Here, OTP mode is excited using direct incidence of white-light-source at normal incidence as well as oblique incidence on M-DBR geometry. The lifetime of OTP in gold and silver deposited films on DBR mirror was determined from OTP resonance linewidth. The lifetime and the Q-factor of OTP modes are found to depend on DBR bilayers, metal film thickness as well as on different plasmon active metals. This finding would facilitate tuning the Q-factor and consequently, the lifetime of OTP modes for various applications in all-optical switches and modulators. In addition, we discuss the spectral characteristics of OTP modes excited using normal and oblique incident of source.